The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/polym14112188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amino Hyperbranched Polymer-Modified Carbon Nanotubes on the Crystallization Behavior of Poly (L-Lactic Acid) (PLLA)

Abstract: Poly-L-lactic acid (PLLA) is an environmentally friendly and renewable polymer material with excellent prospects, but its low crystallization rate greatly limits its application. Through the amidation reaction between amino hyperbranched polymer (HBP N103) and carboxylated carbon nanotubes (CNTs), CNTs-N103 was obtained. The modification was confirmed by Fourier-transform infrared (FTIR) spectroscopy, X-ray electron spectroscopy (XPS) and thermogravimetric analysis (TGA). Using transmission electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…According to TGA results, HBP N102 has a lower grafting rate than HBP H202, which also resulted in more carboxyl groups on the surface of CNTs-N102, so it had a better effect on the improvement of the crystallization performance of PLLA. However, previous studies have shown that we can regulate the grafting rate of HBP on the surface of CNTs by adjusting the molecular weight of HBP …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to TGA results, HBP N102 has a lower grafting rate than HBP H202, which also resulted in more carboxyl groups on the surface of CNTs-N102, so it had a better effect on the improvement of the crystallization performance of PLLA. However, previous studies have shown that we can regulate the grafting rate of HBP on the surface of CNTs by adjusting the molecular weight of HBP …”
Section: Resultsmentioning
confidence: 99%
“…To explore the influence of modified CNTs on the crystallization properties of PLLA, we prepared pure PLLA and PLLA composites with unmodified CNTs, HBP H202-modified CNTs, and HBP N102-modified CNTs, which were named PLLA, PLLA/C, PLLA/C-H, and PLLA/C-N, respectively. In the composites, according to the previous research, we discussed the effect of the concentration of CNTs on the crystallization of PLLA, and the results showed that the 1 wt % concentration of CNTs has the best regularity on the crystallization of PLLA . Therefore, the concentration of unmodified CNTs, HBP H202-modified CNTs, and HBP N102-modified CNTs is 1 wt %.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations